ChemInform Abstract: Solution‐Processable Glass LiI‐Li4SnS4 Superionic Conductors for All‐Solid‐State Li‐Ion Batteries. Issue 19 (April 2016) - Park, Kern Ho; Oh, Dae Yang; Choi, Young Eun; Nam, Young Jin; Han, Lili; Kim, Ju‐Young; Xin, Huolin; Lin, Feng; Oh, Seung M.; Jung, Yoon Seok
Abstract: A new, highly conductive, highly deformable, and dry‐air‐stable glass, 0.4LiI‐0.6Li4 SnS4 is prepared at 200 °C from a homogeneous MeOH solution of Li4 SnS4 (obtained from stoichiometric mixtures of Li2 S and SnS2 at 450 °C) and LiI.